Early Reading Skill Progression Using Illustrated Word Cards: Perkembangan Keterampilan Membaca Awal Menggunakan Kartu Kata Bergambar - Rachma Melanianing arum; Evie Destiana (Academia Open, 2025)
General Background Early childhood education represents a critical foundation for language development, particularly in early reading skills that support later literacy acquisition. Specific Background In kindergarten settings, early reading activities are often limited to conventional board-based instruction, which may not adequately engage children aged 5–6 years in recognizing letters, syllables, and simple sentences. Knowledge Gap There is limited classroom-based evidence describing structured learning cycles that document measurable progression of early reading skills through interactive visual media in Indonesian early childhood institutions. Aims This study aimed to describe the progression of early reading skills among children aged 5–6 years through the use of illustrated word card media in Group B1 of TK Dharma Wanita Jeruk Gamping Krian. Results Using a classroom action research design with two instructional cycles, observational data showed a progressive increase in early reading mastery, from 56.67% at the pre-cycle stage to 72.22% in Cycle I and 88.89% in Cycle II, based on indicators of letter recognition, syllable and word reading, and simple sentence reading. Novelty The study presents a cyclical, activity-based application of illustrated word cards that systematically documents skill progression across learning stages within an authentic classroom context. Implications These findings indicate that structured use of illustrated word card media can support the organization of engaging early reading activities and provide practical guidance for teachers in designing literacy-oriented learning experiences in kindergarten classrooms. Highlights: Progressive Mastery of Letter, Syllable, and Simple Sentence Reading Was Recorded Across Instructional Cycles. Classroom Action Research Cycles Enabled Systematic Observation of Literacy Skill Development. Visual and Hands-on Learning Activities Supported Sustained Learner Engagement During Reading Sessions. Keywords: Early Reading Skills, Illustrated Word Cards, Early Childhood Education, Classroom Action Research, Kindergarten Literacy